Child abuse in Malaysia: An overview from Islamic perspective - Hamdzah, Hazwani; Fatah Yasin, Raudlotul Firdaus (Global Business and Social Entrepreneurship, 2016)
In Islam, children are a monumental trust from Allah (SWT) and parents are mandated with the responsibility to raise and educate them. A well-endorsed treatment is thus a personal and religious imperative. Conversely, maltreatment and abuse are indeed great sins. Hence, this paper seeks to discover an overview of child abuse in Malaysia and how Islam prohibits child abuse by critically analysing existing research works, articles, journals, thesis and books from library and archive. An analysis of Qur’anic verses and interpretations related to prohibition of child abuse, as well as the kind treatment of Prophet Muhammad (PBUH) and his companions towards the children and the youth, is also carried out, which serves as the evidence and living examples of child abuse prevention and its implementation in this modern time in Malaysia. It is expected that this study will be able to create awareness in the society and offer theoretical solutions derived from the original source of knowledge, that is, the Divine Revelation.